How Corporate Social Responsibility Influences Organizational Commitment - Turker, Duygu (Journal of business ethics, 2008)
A growing number of studies have investigated the various dimensions of corporate social responsibility (CSR) in the literature. However, relatively few studies have considered its impacts on employees. The purpose of this study is to analyze how CSR affects the organizational commitment of employees based on the social identity theory (SIT). The proposed model was tested on a sample of 269 business professionals working in Turkey. The findings of the study revealed that CSR to social and non-social stakeholders, employees, and customers were the significant predictors of organizational commitment. However, there was no link between CSR to government and the commitment level of employees.